1997
DOI: 10.1007/s004210050174
|View full text |Cite
|
Sign up to set email alerts
|

Indices of skeletal muscle damage and connective tissue breakdown following eccentric muscle contractions

Abstract: Indirect indices of exercise-induced human skeletal muscle damage and connective tissue breakdown were studied following a single bout of voluntary eccentric muscle contractions. Subjects (six female, two male), mean (SD) age 22 (2) years performed a bout of 50 maximum voluntary eccentric contractions of the knee extensors of a single leg. The eccentric exercise protocol induced muscle soreness (P < 0.05 Wilcoxon test), chronic force loss, and a decline in the 20:100 Hz percutaneous electrical myostimulation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
5
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 34 publications
(37 reference statements)
11
74
5
4
Order By: Relevance
“…Studies 2,3,6,8,[10][11][12]14,18,23,24 emphasizing eccentric exercise have resulted in muscular pain along with decrements in performance. In our study, pressure-pain thresholds were decreased at all time points postexercise, indicating an increase in muscle tenderness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies 2,3,6,8,[10][11][12]14,18,23,24 emphasizing eccentric exercise have resulted in muscular pain along with decrements in performance. In our study, pressure-pain thresholds were decreased at all time points postexercise, indicating an increase in muscle tenderness.…”
Section: Discussionmentioning
confidence: 99%
“…Other DOMS-induced impairments that may reduce athletic performance include decreased joint proprioception, 6 overestimation of force production, 6 decreased joint range of motion, 7 decreased strength and power measures, 8 alterations in agonist and antagonist strength ratios, 9 changes in recruitment patterns, 3 and increased risk of injury. 10 With any combination of these, joint mechanics and muscle function are compromised; thus, individuals adapt compensatory movement patterns, 6 possibly leading to reduced athletic performance.…”
Section: Journal Of Athletic Trainingmentioning
confidence: 99%
“…Previous studies have shown that eccentric exercise induces delayed onset muscle soreness (DOMS) (Jamurtas et al 2000), ultrastructural damage to muscle fibres (Friden 1984), elevation of muscle proteins in the circulation (Nosaka and Clarkson 1995), and decrement in range of motion (ROM) and force . Muscles that are primarily utilized to evaluate the effects of eccentric exercise on these markers of muscle damage are the knee extensors (Brown et al 1997;Hortobagyi et al 1998) and the elbow flexors (Newham et al 1988;Nosaka et al 1991;Paddon-Jones and Abernethy 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, without measuring lactate, we can only assume that this phenomenon may be caused by a decrease of aerobic metabolism and subsequent increases of anaerobic metabolic activities at a late stage of a process of eccentric exercise modes that exceed the current physical conditioning of the tendon. Because eccentric muscle contractions were found to increase collagen breakdown in the patellar tendons, 4 increases in anaerobic metabolism (when tendons are becoming compliant through exercise) may be related to maintaining a low metabolic rate without the risk of ischemia and necrosis 9 and favoring collagen synthesis. 30 However, this anaerobic metabolism may also lead to slow recovery (or healing) following activity.…”
mentioning
confidence: 99%